Co-management institutions, knowledge, and learning: Adapting to change in the Arctic - Berkes, Fikret; Armitage, Derek (Études/Inuit/Studies, 2010)
AbstractHow vulnerable are Arctic Indigenous peoples to climate change? What are their relevant adaptations, and what are the prospects for increasing their ability to deal with further change? The Intergovernmental Panel on Climate Change makes little mention of Indigenous peoples, and then only as victims of changes beyond their control. This view of Indigenous peoples as passive and helpless needs to be challenged. Indigenous peoples, including the Canadian Inuit, are keen observers of environmental change and have lessons to offer about how to adapt, a view consistent with the Inuit self-image of being creative and adaptable. There are three sources of adaptations to impacts of climate change: 1) Indigenous cultural adaptations to the variability of the Arctic environment, discussed here in the context of the communities of Sachs Harbour and Arctic Bay; 2) short-term adjustments (coping strategies) that are beginning to appear in recent years in response to climate change; and 3) new adaptive responses that may become available through new institutional processes such as co-management. Institutions are related to knowledge development and social learning that can help increase adaptive capacity and reduce vulnerability. Two co-management institutions that have the potential to build Inuit adaptive capacity are the Fisheries Joint Management Committee (established under the Inuvialuit Final Agreement), and the Nunavut Wildlife Management Board.